Assessment of Some Hematological and Biochemical Parameters of Diesel Generator Workers in Al-Diwaniyah Province, Iraq - Anbaki, Ali Abdul Ameer Al (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Continuous exposure to pollutants from diesel generators may cause numerous health problems. The current study aimed to determine the effects of diesel generators on workers by examining hematological and biochemical parameters. Methods: The current study was conducted on diesel generator workers in Al-Qadisiyah Governorate. The study consisted of approximately (50) individuals divided into two groups: the first group (25) workers, and the second group (25) healthy individuals (as a control group). The parameters studied included blood parameters (red blood cells, hemoglobin, and pneumococcal size), as well as biochemical tests, including liver function tests (AST, ALT, and ALP), and kidney function tests, including (urea, creatinine, and total protein). Results: The results indicated significant changes (P<0.05) in biochemical parameters. There was a significant increase (P<0.05) in red blood cell count, hemoglobin, pneumococcal volume, liver function tests (ALT, ALP, AST), urea-creatinine, total cholesterol, and triglycerides. The study results also showed a significant decrease (P<0.05) in total protein concentration in generator workers when compared to the healthy group. Conclusion: Direct exposure to pollutants by generator workers may lead to changes in their blood and biochemical parameters because it targets important sites in the body, especially the bone marrow, kidneys, liver, and other organs. Highlights: Diesel generator workers exhibit significant alterations in hematological and biochemical parameters compared to the control group. Exposure to generator pollutants increases red blood cell count, liver enzymes (ALT, AST, ALP), and kidney markers (urea, creatinine). Reduced total protein levels highlight the adverse effects of prolonged pollutant exposure on overall health. Keywords : Study, Hematological, Biochemical Parameters, Diesel Generator, Al-Diwaniyah